Copper accumulation in vineyard soils: Rhizosphere processes and agronomic practices to limit its toxicity. (November 2016) - Brunetto, Gustavo; Bastos de Melo, George Wellington; Terzano, Roberto; Del Buono, Daniele; Astolfi, Stefania; Tomasi, Nicola; Pii, Youry; Mimmo, Tanja; Cesco, Stefano
Abstract: Viticulture represents an important agricultural practice in many countries worldwide. Yet, the continuous use of fungicides has caused copper (Cu) accumulation in soils, which represent a major environmental and toxicological concern. Despite being an important micronutrient, Cu can be a potential toxicant at high concentrations since it may cause morphological, anatomical and physiological changes in plants, decreasing both food productivity and quality. Rhizosphere processes can, however, actively control the uptake and translocation of Cu in plants. In particular, root exudates affecting the chemical, physical and biological characteristics of the rhizosphere, might reduce the availability of Cu in the soil and hence its absorption. In addition, this review will aim at discussing the advantages and disadvantages of agronomic practices, such as liming, the use of pesticides, the application of organic matter, biochar and coal fly ashes, the inoculation with bacteria and/or mycorrhizal fungi and the intercropping, in alleviating Cu toxicity symptoms. Highlights: Speciation of Cu in soil solution is crucial to determine its toxicity to organisms. Root exudation is involved in both Cu exclusion and Cu accumulation in plants. Agronomic practices might either alleviate or exacerbate Cu toxicity